Development-led archaeology in northwest Europe : proceedings of a round table at the University of Leicester, 19th-21st November 2009 - Webley, Leo; Bats, Machteld (Oxbow Books, 2012)
Many countries in northern Europe have seen a huge expansion in development-led archaeology over the past few decades. Legislation, frameworks for heritage management and codes of practice have developed along similar but different lines. The Valetta Convention has had considerable impact on spatial planning and new legislation on archaeological heritage management within EC countries as well as on the funding, nature and distribution of archaeological fieldwork. For the first time these 12 papers bring together data on developer-led archaeology in Britain, Ireland, France, the Low Countries,